1995
DOI: 10.4102/sajip.v21i3.594
|View full text |Cite
|
Sign up to set email alerts
|

Towards establishing biographical and business background profiles of entrepreneurs from two ethnic and gender groups

Abstract: The literature on the biographical backgrounds of entrepreneurs seems to contain many contradictory findings. This situation can partly be due to the assumption that samples of entrepreneurs were homogeneous rather than heterogeneous. It appears as if female entrepreneurs have been less well researched than their male counterparts. Differences in the biographical backgrounds and business situation of, respectively, the white and the black entrepreneurs in South Africa have been assumed but little empirical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The uneven distribution of business ownership between males and females could to a considerable extent be attributed to entry barriers experienced by females in particular, for example insufficient access to finance and credit facilities (Brown, 1997;Kolvereid et al, 1993, Maysami & Goby, 1999, Schutte et al, 1995, World Bank Group, 1999. Contrary to the general trend, the UK study of Rosa et al (1994) did not support the view that there is discrimination against women when it comes to bank loan applications.…”
Section: Problems Facing Female Entrepreneursmentioning
confidence: 99%
“…The uneven distribution of business ownership between males and females could to a considerable extent be attributed to entry barriers experienced by females in particular, for example insufficient access to finance and credit facilities (Brown, 1997;Kolvereid et al, 1993, Maysami & Goby, 1999, Schutte et al, 1995, World Bank Group, 1999. Contrary to the general trend, the UK study of Rosa et al (1994) did not support the view that there is discrimination against women when it comes to bank loan applications.…”
Section: Problems Facing Female Entrepreneursmentioning
confidence: 99%
“…In the past, a number of studies have examined the motivations and challenges of women entrepreneurs (Jennings and Brush, 2013; Pandey, 2013; Richardson, 2004; Singh, 1993). The literature on motivations and challenges has lately acknowledged the importance of analyzing women entrepreneurship from the institutional perspective as institutions create opportunities but at the same time, may also pose challenges for women entrepreneurs if major institutional deficiencies exist (Andriuta and Kartašova, 2013; Bui et al , 2018; Kamalanabhan and Vijaya, 2008; Schutte et al , 1995;). Despite its relevance, the institutional theory standpoint is under-exploited in the literature on women’s entrepreneurship (Bui et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In his studies relating to entrepreneurship Matlay (2006) posited that conceptual and contextual convergence is of paramount importance to the ongoing debate of whether entrepreneurs are born or made and to issues surrounding entrepreneurship education and its impact on entrepreneurial activities. Schutte (1995) suggested that the male entrepreneurs have been extensively studied and the focus has now shifted to the study of female entrepreneurs. Hisrich and Brush (1984) mentioned that most of what is known about entrepreneurs, their background, motivation for starting a business and business problems faced by them are based on studies of male entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%